Tolosa-Hunt Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
The authors report a case in a 10.5 year old girl admitted to the Centre hospitalier Guy-de-Chauliac, Montpellier, France, with a left painful ophthalmoplegia.